New capabilities of plasma potential and density measurements using a dual heavy ion beam probing (HIBP) diagnostic in the TJ-II stellarator - Zhezhera, A.I.; Chmyga, A.А.; Deshko, G.N.; Eliseev, L.G.; Hidalgo, C.; Komarov, A.D.; Kozachek, A.S.; Krupnik, L.I.; Melnikov, A.V.; de Pablos, J.L.; Perfilov, S.V. (Вопросы атомной науки и техники, 2017)
The unique capabilities of the dual HIBP system allow the investigation of multi-scale mechanisms to be expanded from the plasma edge to the plasma core in the TJ-II stellarator. Experiments with combined NBI and ECRH heating have shown direct experimental evidence of the influence of ECRH on turbulent mechanisms, increasing the level of fluctuation, on the amplitude of Long-Range-Correlations (LRC) as proxy of Zonal Flows (ZFs) for potential fluctuations but not for density and poloidal magnetic fluctuations and on neoclassical radial electric fields. Whereas ECRH influences the level of fluctuations in a wide range of plasma densities, ECRH induced reversal of the neoclassical radial electric field has been observed only in low-density plasmas. The TJ-II unique experimental capabilities would allow validation of nonlinear saturation of turbulence simulations (e.g. TEM), including quantitative assessments of discrepancies (e.g. level of fluctuations, correlation lengths and interplay with ZFs) between theoretical and experimental results. Уникальные возможности двойной системы ЗПТИ позволяют расширить исследование влияния мульти-масштабных механизмов удержания от границы до центра плазмы в стеллараторе TJ-II. Эксперименты с комбинированным нагревом нейтральным пучком и электронно-циклотронным резонансом (ЭЦР) показали прямое экспериментальное доказательство влияния ЭЦР на турбулентные механизмы, приводящие к увеличению уровня флуктуаций, амплитуды дальних корреляций (как показатель зональных течений) для колебаний потенциала, неоклассического радиального электрического поля, но не для колебаний плотности плазмы и полоидального магнитного поля. В то время как ЭЦР влияет на уровень флуктуаций в достаточно широком диапазоне плотностей плазмы, индуцированный ЭЦР-переворот неоклассического радиального электрического поля наблюдается только для плазмы с низкой плотностью. Уникальные экспериментальные возможности TJ-II позволили бы проверку численного моделирования нелинейного насыщения турбулентности (например, TEM), включая количественные оценки в расхождении (например, амплитуды колебаний, длины корреляции и их взаимодействие с зональными потоками) между теоретическими и экспериментальными результатами. Унікальні можливості подвійної системи ЗПВІ дозволяють розширити дослідження впливу багатомасштабних механізмів утримання з периферії до центру плазми в стелараторі TJ-II. Експерименти з комбінованим нагрівом нейтральним пучком і електронно-циклотронним резонансом (ЕЦР) показали пряме експериментальне підтвердження впливу ЕЦР на турбулентні механізми, що приводять до збільшення рівня флуктуацій, амплітуди далеких кореляцій (як показник зональних течій) для коливань потенціалу, неокласичного радіального електричного поля, але не для коливань густини плазми і полоідального магнітного поля. У той час як ЕЦР впливає на рівень флуктуацій в досить широкому діапазоні густини плазми, індукований ЕЦР-переворот неокласичного радіального електричного поля спостерігається тільки для плазми з низькою густиною. Унікальні експериментальні можливості TJ-II дозволили б перевірку чисельного моделювання нелінійного насичення турбулентності (наприклад, TEM), включаючи кількісні оцінки в розходженні (наприклад, амплітуди коливань, довжини кореляції і їх взаємодія з зональними потоками) між теоретичними і експериментальними результатами.